Pregnancy in Classical Paroxysmal Nocturnal Hemoglobinuria and Aplastic Anemia–Paroxysmal Nocturnal Hemoglobinuria: A High-Risk Constellation - Alashkar, Ferras; Saner, Fuat H.; Vance, Colin; Schmücker, Ute; Herich-Terhürne, Dörte; Dührsen, Ulrich; Köninger, Angela; Röth, Alexander (Frontiers in Medicine, 2020)
Pregnancies in paroxysmal nocturnal hemoglobinuria (PNH) are associated with increased morbidity and mortality. Retrospective studies suggest that outcome has improved with the advent of the complement inhibitor eculizumab. To substantiate this assumption we analyzed the data from patients treated in our department since 2009. All patients were included in the International PNH registry and followed prospectively. We identified 16 pregnancies in 9 patients with classical PNH, and two pregnancies in two patients with aplastic anemia (AA)-PNH. In classical PNH, 13 pregnancies were supported by eculizumab. Break-through hemolysis occurred in six pregnancies, necessitating an increase in the biweekly eculizumab dose from 900 mg to 1200 - 1800 mg. Red blood cell transfusions were given in six and platelet transfusions in two pregnancies. A Budd-Chiari syndrome and cholecystitis complicated the course of two pregnancies. Four of 13 pregnancies supported by eculizumab ended in spontaneous abortion or stillbirth, and one was prematurely terminated because of fetal trisomy 21. None of the three pregnancies not supported by eculizumab had a successful outcome. Half the deliveries were preterm. None of the patients died, and, in all but one patient, the postpartum period was uneventful. Both pregnancies in patients with AA-PNH took a favorable course. Our results confirm low maternal mortality and frequent break-through hemolysis in pregnant PNH patients receiving eculizumab. Fetal mortality and the rate of preterm delivery were higher than reported previously, possibly related to the use of registry data that are likely to reduce the risk of publication and recall biases.